Empirical investigation of biometric, non-visible, intra-signature features in known and simulated signatures. Issue 6 (1st November 2016) - Dewhurst, Tahnee N.; Ballantyne, Kaye N.; Found, Bryan
Abstract : With the continued proliferation of electronic point of transaction signature recording devices, research into biometric indicators of spurious handwriting is attracting increasing interest. Whilst many investigations have focused on the static and dynamic indications of known or spurious behaviour in handwriting, little empirical research is available regarding the identification of such writings through the analysis and comparison of non-visible, intra-signature, kinematic parameters. These features are associated with segments within a signature formation where the pen is momentarily lifted from the page, such as might occur between a first and last name, or when the pen is lifted from the page for the purpose of crossing a 't' or dotting an 'i'. It is postulated that this type of feature analysis may be of value in support of examiners' static examinations of disputed writings, and subsequent formation of opinion as to genuineness or otherwise. To investigate this, 13 skilled writers generated 195 known signature formations, which were then simulated 1560 times by eight simulators. All signatures, known and simulated, were simultaneously captured both statically and dynamically. The presence of non-visible features in the known signatures was recorded, analysed and compared with the prevalence of similar features in the simulation attempts. The duration, absolute size, straightness error and jerk (disfluency measure) of the extracted segments were examined and compared, with the result that simulated signatures showed an increase in all the above parameters, compared with the known signatures. Furthermore, the visualised representation of the non-visible, intra-signature segments illustrated an overall gross pictorial disparity between the known and simulated signatures, which may be of use during first pass authenticity examinations.